Microencapsulação por Spray drying de ácido benzoico e óleo essencial de tomilho - Marques, Gerson Reginaldo (2016)
The objective of this work was to verify the influence of the drying conditions and encapsulating materials over the physical and physical-chemical characteristics of the microparticles of benzoic acid and thyme essential oil. In the microencapsulation of benzoic acid, we used a central rotational composite design, using the independent variables: drying air entry temperature (145 oC – 180oC) and concentration of the benzoic acid (2% - 10% (m/m)). The drying temperature and concentration of benzoic acid significantly influenced the physical and morphological parameters of the microparticles. The parameters for atomization drying of benzoic acid indicated that the temperature of 169oC and the concentration of 6% (m/m) of benzoic acid were the best processing conditions for obtaining microencapsulated benzoic acid, using as encapsulating matrix modified starch and maltodextrin. A second experiment was conducted using a completely randomized design with three replicated, with the treatments modified starch (MS), maltodextrin (M) and a mixture of modified starch and maltodextrin (MS/M). The application of the mixture of these encapsulating materials (MS/M) resulted in high encapsulating efficiency (82.65 g/100g). The morphology of the MS/M treatment presented partially rough microparticle, and treatments MS and M resulted in the formation of a larger amount of brittle microparticles. The diameter of the microparticle of the MS/M powder resulted in a value of 19.15 µm and the span, which indicates good homogeneity of the microparticles ranged from 1.94 to 2.15. The isotherm presented Type III behavior for the MS/M treatment and the GAB mathematical model was the best adjusted to the experimental data for microparticle moisture sorption behavior. The viscosity of the thyme essential oil emulsion was evaluated in all treatments (WPI – Whey protein isolate; WPIM – Whey protein isolate and maltodextrin; WPIM1C – Whey protein isolate, maltodextrin and 1% chitosan and WPIM2C – Whey protein isolate, maltodextrin and 2% chitosan) using the Herschel Bulkley model. A third experiment was done to evaluate the WIP material in different blends of encapsulants (WIPM, WIPM1C and WIPM2C).In the microencapsulation of the thyme essential oil, the treatment with WIPM presented better characteristics for the resulting product: 9.24 g/100g for hygroscopicity, 60.62 g/100g for solubility and its morphology presented spherical surfaces. We verified that the efficiency of the microencapsulation process of treatment WIPM presented high oil retention (29.50%), when compared to treatment WIP (28.62%) and WIPM1Q (23.75%). The evaluation studied for the principal components indicated that thymol was characterized as major constituent of the thyme essential oil, with contents above 40% of the normalized area, being this important characteristic to exert antioxidant activity.